ECOLINGUISTICS AND THE EDUCATION OF YOUNG PEOPLE - Roe, Jasper; Chenghao, Zhu; Huat, Chau Meng; Qingli, Guo; Jacobs, George (English Education Study Programme of Sanata Dharma University, Yogyakarta, Indonesia, 2023)
Most ecolinguistic analysis is conducted with texts produced for the general public. This article explores the use of ecolinguistics in the education of young people. The analysis focuses on young people’s media, specifically focusing on films. Two children’s movies (The Lorax and Back to the Outback) are analyzed using the ecolinguistic concept of stories we live by and the ecojustice concept of intersectionality. This analysis is undertaken to explicate these concepts in the hope that others will employ these same concepts to analyze other texts. These example analyses are explained about classroom practice and generating “noticing” as a learning outcome. Finally, five further techniques for involving students and others in ecolinguistic and ecojustice analysis are described. This article gives important insight into practical tools that can benefit teachers and students in the classroom. Additionally, children’s films and other media developed for children and youths may also be useful for the enjoyment and education of adults.